2020
DOI: 10.21203/rs.3.rs-96637/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptions, emotional reactions and needs of adolescent psychiatric inpatients during the COVID-19 pandemic: A qualitative analysis of in-depth interviews

Abstract: Background: The new coronavirus pandemic (COVID-19) has been accompanied by great psychological pressure on the entire population. However, little is known about how this pandemic could affect the more vulnerable population with severe mental illness.Aims: To explore adolescent psychiatric inpatients' perceptions, emotional reactions and needs during the first wave of the COVID-19 pandemic.Methods: Individual in-depth interviews were conducted with nine psychiatric inpatients aged 12-17 years. Five themes were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…An online survey of 442 Greek senior high school students conducted in April 2020 revealed a rise in depression and anxiety levels in the time of home confinement (Giannopoulou et al, 2021 ). A qualitative study investigating the impact of the pandemic through individual interviews with nine psychiatric inpatient adolescents in a paediatric hospital in Athens reported anxiety about harm to self and beloved ones (Giannakopoulos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An online survey of 442 Greek senior high school students conducted in April 2020 revealed a rise in depression and anxiety levels in the time of home confinement (Giannopoulou et al, 2021 ). A qualitative study investigating the impact of the pandemic through individual interviews with nine psychiatric inpatient adolescents in a paediatric hospital in Athens reported anxiety about harm to self and beloved ones (Giannakopoulos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the identification of feelings experienced during hospitalization, 71.9% (n = 23) of the articles indicated that the patients and family members experienced difficult moments 47 during the hospitalization period, with feelings of loneliness 16,17,21,31 and isolation 16,17,21,29,31,40,41 due to the restrictions regarding visits and companions and a lack of contact between professionals and patients. 20 Feelings such as sadness, 23,26,46 fear, 17,18,20,22,[24][25][26][27][28][29]32,33,46 anxiety, 17,22,28,38,41,46 worry, 17,[20][21][22][23][24]32,33,46 nervousness, 22 guilt, 26,46 anger, 23,…”
Section: Concern About the Patient's Well-being During Hospitalizationmentioning
confidence: 99%
“…25 As for welcoming of the team during hospitalization, 68.8% (n = 22) of the articles addressed how the team was treated, highlighting attitudes of kindness, 17,31 empathy, 17,28 courtesy, 25 respect, 25,45 sympathy, 28,29 understanding, 29 compassion, 31 professionalism, 24,31 communication, 21 and attention and patience. 34 Attitudes like these were associated with an improvement in the patients' state of mind 17 and with a sense of security, 18,23,46 making a difference to patient satisfaction. [28][29][30][31] Furthermore, in one of the studies, 94.7% of the patients reported having received support from the maternity team.…”
Section: Concern About the Patient's Well-being During Hospitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies relating to psychosocial effects of the pandemic on children and adolescents are prolific and continually increasing (see Chawla et al, 2021; Meherali et al, 2021), there are still notable knowledge gaps. Many studies are limited to needs of a specific group, often those with particular morbidities or life-situations (see Giannakopoulos et al, 2021; Mirlashari et al, 2021; Sharma et al, 2020; Tse et al, 2021). In addition, only a minority of studies are based on data generated directly by children or adolescents, with most instead relying on proxy reports from teachers, parents and other sources (Berasategi Sancho et al, 2021; Evans et al, 2020; Ferrari et al, 2021; Ferraro et al, 2021; Fitzpatrick et al, 2020).…”
Section: Introduction and Aimmentioning
confidence: 99%